Predicting the polyspecificity of aminoacyl-tRNA synthetase for non-canonical amino acids using molecular dynamics simulation and MM/PBSA. - Dongheon Lee; Jong-Il Choi (PLoS ONE)
With the advancement of genetic code expansion, the field is progressing towards incorporating multiple non-canonical amino acids (ncAAs). The specificity of aminoacyl-tRNA synthetases (aaRSs) towards ncAAs is a critical factor, as engineered aaRSs frequently show polyspecificity, complicating the precise incorporation of multiple ncAAs. To address this challenge, predicting binding affinity can be beneficial. In this study, we expressed sfGFP using an orthogonal aaRS/tRNA pair with 4-Azido-L-phenylalanine (AzF) and another four different ncAAs. The experimental results showed specificity with O-Methyl-L-tyrosine as well as AzF, and these results were compared with computational predictions. We constructed a mutant aaRS structure specific for AzF through homology modelling and conducted docking studies with tyrosine and five ncAAs, followed by molecular dynamics simulations. The binding affinity was calculated using the molecular mechanics/Poisson-Boltzmann surface area, focusing on nonpolar solvation terms. While the analysis is based on the incorporation of limited number of ncAAs, the cavity and dispersion term method showed consistency with experimental data, highlighting its potential utility compared to the surface area term method. These findings enhance understanding of the ncAA specificity of aaRS in relation to computer simulations and energy calculations, which can be utilized to rationally design or predict the specificity of aaRS.